Working life patterns after sickness absence due to depression: A 15-year register-based prospective cohort study - Stutaite, Gerda; Mittendorfer-Rutz, Ellenor; Helgesson, Magnus; Kautzky, Alexander; Finnes, Anna; Gémes, Katalin (Journal of affective disorders, 2025)
To identify working life patterns after sickness absence (SA) due to depression and sociodemographic, work, and health-related factors associated with them. The study cohort included 9139 Swedish residents, aged 25–40, with a new SA spell due to depression in 2005. We followed the cohort for 15 years analyzing their yearly dominant labor market outcomes. Sequence analysis was used to identify distinct labor market sequences and cluster analysis – to group similar sequences into working life typologies. For the sociodemographic, work, and health-related factor analysis, we used multinomial logistic regression. We identified 4373 sequences and seven typologies: 1) “Predominant Economic Activity (EA)” (70.7 %), 2) “Predominant EA with Intermittent SA/Disability Pension (DP)” (14.4 %), 3) “Predominant Long-Term SA/DP” (8.0 %), 4) “Long-Term SA/DP Followed by No EA” (2.2 %), 5) “SA/DP with Some EA” (1.6 %), 6) “Emigration” (1.7 %), and 7) “Death” (1.4 %). Factors associated with the predominant long-term SA/DP typology included birth outside Sweden (OR = 1.61, 95 % CI: 1.29–2.01), lower educational attainment (OR = 3.20, 95 % CI: 2.42–4.22), prolonged index SA spell due to depression (OR = 4.81, 95 % CI: 3.71–6.25), prior long-term SA (OR = 3.60, 95 % CI: 2.87–4.50) and unemployment (OR = 2.00, 95 % CI: 1.61–2.48). Living with children (OR = 0.68, 95 % CI: 0.56–0.82) was associated with lower odds of belonging to this typology. Most individuals after SA due to depression maintained their engagement in the labor market suggesting that Sweden's welfare system is supportive of their workforce participation. However, some individuals belonged to long-term SA, DP, and lack of EA typologies indicating a potential path to labor market marginalization. •Most individuals were active in the labor market post sick leave due to depression.•Some had working life patterns indicating potential labor market marginalization.•Education and living with children were linked to higher labor market engagement.•Prior sick leave and unemployment were linked to lower labor market engagement.•Sequence analysis can capture complex patterns after sick leave due to depression.